Gadgets and Their Impact on The Development of Religious and Moral Values (International Journal of Active Learning, 2023)
Gadgets are one of the advanced technologies and are needed by many people today. From parents to children, the use of gadgets is commonplace. Today almost all early childhood has used gadgets. The time in using gadgets  should be set as efficiently as possible The purpose of this study is to find out how long the use of  gadgets is and the impact of  gadget  use on the development of religious and moral values in early childhood. in Group A BA Aisyiyah Tanjungsari. The research uses quality research with a descriptive approach. In collecting research data using interview techniques, time observation and documentation. The results of the study conducted in group A BA Aisyiyah Tanjungsari which numbered 30 children showed that the duration of  gadget use was included in the low use category between 01-30 minutes as many as 15 children, the  medium category around 30-60 minutes as many as 10 children, the high category with the use of more than 60 minutes as many as 5 children. The impact of the use of  gadget on the development of religious and moral values in  Group A children in BA Aisyiyah Tanjungsari has a positive impact by achieving indicators of the development of religious and moral values.